Dynamical model for individual defence against cyber epidemic attacks. (1st November 2019) - Yan, Dingyu; Liu, Feng; Zhang, Yaqin; Jia, Kun
Abstract : When facing the on‐going cyber epidemic threats, individuals usually set up cyber defences to protect their own devices. In general, the individual‐level cyber defence is considered to mitigate the cyber threat to some extent. However, few previous studies focus on the interaction between individual‐level defence and cyber epidemic attack from the perspective of dynamics. In this study, the authors propose a two‐way dynamical framework by coupling the individual defence model with the cyber epidemic model to study the interaction between the network security situation and individual‐level defence decision. A new individual‐based heterogeneous model for cyber epidemic attacks is established to emphasise the individual heterogeneity in defence strategy. In the meanwhile, a Markov decision process is used to characterise the defence decision in the individual defence decision model. The theoretical and numerical results illustrate that the individual‐level defence can dampen the cyber epidemic attack, but the current network security situation, in turn, influences the individual defence decision. Moreover, they obtain a glimpse of the network security situation and the individual defence with respect to different cyber epidemic scenarios.